Direktorjev položaj v korporacijskem in obligacijskem pravu - Ocepek, France (Podjetje in delo, 2014)
The article discusses manager`s status on the theoretical level (law in books) and on the level of realized law in court decisions (law in action). The managerial corporate position is critically evaluated according to the theory and praxis, where questions of the nullity of supervisory board resolutions and the possibility of reintegrating manager after his recall are addressed. The functional link between corporate and obligational relationship emphasizes the questionability of court jurisdictional divisions. In Slovenia, the obligational part of relationship is in most cases regulated by an employment contract, even though theory almost unanimously agrees that the manager could have an employee status only in limited circumstances. Court decisions and theory are critically evaluated due to the new law on employment relationships. The new law clearly supports freedom of contract instead of contract substance primacy regarding the definition of contractual relation. The praxis about dissolutions of employment contract is well established, but the connection to corporate litigations has not been clarified yet. The courts have already gone through the complexity of managers` legal statuses and decided in liability cases that manager duties are of a corporate nature - not of an employment. Danosa case could point to a new approach to employment rights of a manager. One possibility for future manager rights` protection could be the legal institute of an economically dependent person.
Keywords: direktorji; gospodarske družbe; korporacije; managerji; pravni položaj